Using Interactive Teaching Strategies in Large Lectures: Some Personal Reflections - Diana Henriss-Anderssen (Legal Education Review)
The Market Day Project is a series of activities aimed at giving students a number of different perspectives on legal disputes involving consumers, and at engaging them in the complexities of a life-like situation. In the early activities the students play the roles of consumers and retailers and, in effect, create their own disputes. In later activities, the students act as the lawyers for the consumers and retailers, isolating the legally relevant facts from the earlier role-plays, negotiating with the other disputants, and providing legal advice. The project involves a broad range of activities and focuses on developing a number of different skills. The students work in groups, which requires communication and planning skills. Some activities involve creativity, such as preparing a product advertisement. Others encourage dramatic skills, such as role-playing the pressured salesperson during the purchase transaction. Later activities develop factual analysis, negotiation and written communication skills. Each activity builds on the previous activities, keeping students engaged with the development of the dispute throughout the project. Although developing the project took substantial work and time, the actual running of the activities is surprisingly easy. Student feedback has been overwhelmingly positive, and it appears that the project has improved learning outcomes in the subject and in particular has increased students’ application skills.